Magic tree house: christmas in Camelot - Osborne, Mary Pope (New York: Random House, 2001)
On Christmas Eve, Jack and Annie's tree house transports them to King Arthur's castle at Camelot, where they undertake a quest to the castle of the Otherworld
Keywords: Magic Fiction -- Magic Juvenile fiction -- Siblings Fiction